Research Progress on Separation, Purification, Structure Analysis and Function of Melanoidins from Plants - Yifei ZHAO; Rentang ZHANG; Jingyan YAN; Jing LIU (Shipin gongye ke-ji, 2023)
In recent years, melanoidins has attracted increasing attention for its biological functions such as anti-cancer, obesity prevention and gut microbiota regulation. This paper reviews the applications of macroporous resin, ultrafiltration, and chromatographic technology in the separation and purification, the adhibition of ultraviolet-visible spectrum, infrared spectrum, fluorescence spectrum, gas chromatography-mass spectrometry, atomic force microscope, nuclear magnetic resonance, atomic force microscope in structure identification, and the function of its cell toxicity, obesity prevention and gut microbiota regulation, anti-cancer. It is expected to stimulate new ideas on the structure, function and safety of melanoidins.